Fast Track Sebagai Upaya Peningkatan Kualitas Penerimaan Calon Mahasiswa Unggul Program Magister Prodi Pendidikan Bahasa Jawa - Ekowati, Venny Indria; Widyastuti, Sri Harti; Endraswara, Suwardi; Reyhana, Vindy; Yuliana, Annisa (Piwulang : Jurnal Pendidikan Bahasa Jawa, 2023)
Fast Track is a superior program that has been implemented at various universities in Indonesia. However, this program which prioritizes effectiveness in completing undergraduate to postgraduate studies has never been implemented in the Javanese Language Education Study Program at UNY. This research aims to prepare an analysis of the need for implementing the fast-track program in Master's and Doctoral Javanese Language Education Study Programs, and develop Standard Operating Procedures (SOP) in the context of implementing the fast-track program to encourage the acceptance of new students in superior categories in the UNY PTNBH era with a hoplological perspective. This research uses educational ethnographic qualitative research methods. Data was collected by distributing questionnaires, interview techniques, observation, and documentation. The data analysis techniques used are data collection, data reduction, presentation of educational ethnographic data, and concluding. Data validity was carried out using triangulation techniques. Based on the research that has been carried out, the following results have been mapped: an analysis of the needs and interests of Javanese Language Education Study Program undergraduate students in participating in the fast track program has been mapped SOPs have been prepared for the implementation of the fast track program. The SOP is prepared based on needs analysis, comparison of fast-track implementation, and interviews with universities that have implemented fast-track programs.